Two prospective Li-based half-Heusler alloys for spintronic applications based on structural stability and spin-orbit effect - Zhang, R. L.; Damewood, L.; Zeng, Y. J.; Xing, H. Z.; Fong, C. Y.; Yang, L. H.; Peng, R. W.; Felser, Claudia (Journal of Applied Physics, 2017)
To search for half-metallic materials for spintronic applications, instead of using an expensive trial-and-error experimental scheme, it is more efficient to use first-principles calculations to design materials first, and then grow them. In particular, using a priori information of the structural stability and the effect of the spin-orbit interaction (SOI) enables experimentalists to focus on favorable properties that make growing half-metals easier. We suggest that using acoustic phonon spectra is the best way to address the stability of promising half-metallic materials. Additionally, by carrying out accurate first-principles calculations, we propose two criteria for neglecting the SOI so the half-metallicity persists. Based on the mechanical stability and the negligible SOI, we identified two half-metals, β-LiCrAs and β-LiMnSi, as promising half-Heusler alloys worth growing.
CRIS-Team Scopus Importer:2022-04-14